Time decay of pulse current in capillary glow discharge - Muayad Ahmed (College of Education for Pure Sciences, 2020)
A high voltage pulse generator was development and implemented. It generates a sequence spike pulses with a varying pulse height from 0 to 5 kV; and changes the pulse width in ms range. This generator tested and used to study the pulse glow discharge in argon by using the capillary tube under pressure 0.3 to 0.5 torr. This study was to establish the nature of discharge relaxation (plasma relaxation) when a high voltage pulse causes a breakdown in the gas (coverts to conducting case). It is of great importance to answer the following question. The current can decay when the voltage pulse is switched off was obtained. The electronic switching is a successful tool which can be used for generating high voltage pulses with flexibility adjustable peak height voltage pulse, pulse duration and pulse width is presented Interesting results concerning because plasma is a function of time, linearity of time decay vs. plasma. This linearity is to seem independent on gas pressure or pulse width. The slope the current decay line is very much dependent upon the initial high voltage pulse. The condition for transition from pulse to continue like DC glow discharge condition is satisfied.